PENGARUH INTELLECTUAL CAPITAL DAN STRUKTUR KEPEMILIKAN TERHADAP KINERJA KEUANGAN: (Studi Empiris pada Perusahaan Pertambangan yang Terdaftar di BEI Selama Tahun 2015-2018) (Jurnal Riset Akuntansi dan Bisnis Indonesia, 2022)
This study aims to examine the effect of intellectual capital and ownership structure on company performance. The sample of this study is mining companies listed on the Indonesia Stock Exchange Period 2015-2018 with a sampling method using purposive sampling of 18 companies. Hypothesis testing is done by using multiple linear regression analysis. The results showed that human capital, structure capital, employee capital, managerial ownership and institutional ownership together influenced ROA. The contribution of human capital, structure capital, employee capital, managerial ownership and institutional ownership together affected ROA of 43.9%. Partially, human capital has a negative effect on Return On Assets (ROA), structure capital has a positive and significant effect on Return On Assets (ROA), employee capital has no effect on Return On Assets (ROA), managerial ownership has a negative effect on Return On Assets (ROA), institutional ownership has a positive and significant effect on Return on Assets (ROA).
Keywords: human capital; structure capital; employee capital; managerial ownership structure; institutional ownership structure; Return on Assets (ROA)